Faktor Penentu Akuntabilitas Keuangan Daerah: Analisis Moderasi SPI - Afthon Azharul Umam; Zulfikar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of fiscal decentralization, dependence on the central government, regional financial management, and regional government performance on the accountability of regional financial reports, as well as the moderating role of the Internal Control System (ISC) in this relationship. This study uses a positivistic quantitative approach with cross-section data from 35 regional governments in Central Java Province during 2019–2023, obtained through documentation of financial reports and government audit results. Accountability is measured based on audit opinions, and ISC serves as a moderating variable. Analysis techniques include descriptive statistics, classical assumption tests, moderation regression, and hypothesis tests. The results show that fiscal decentralization, financial management, and regional government performance have a significant positive effect on accountability, while dependence on the central government has a significant negative effect. ISC moderates these relationships differently: weakening the positive effect of the first three variables, but strengthening the negative effect of dependence on the central government. Overall, all variables and their interactions are proven to significantly affect accountability. These findings emphasize the importance of strengthening proportional ISC and optimizing fiscal decentralization in order to improve transparency and accountability of regional finances.